2016
DOI: 10.2147/idr.s95050
|View full text |Cite
|
Sign up to set email alerts
|

Lemierre’s syndrome: current perspectives on diagnosis and management

Abstract: This is a systematic review of cases with Lemierre’s syndrome (LS) in the past 5 years. LS is characterized by sepsis often evolving after a sore throat or tonsillitis and then complicated by various septic emboli and thrombosis of the internal jugular vein. Symptoms include sepsis, pain, and/or swelling in the throat or neck, as well as respiratory symptoms. Laboratory findings show elevated infectious parameters and radiological findings show thrombosis of the internal jugular vein and emboli in the lungs or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
194
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(209 citation statements)
references
References 88 publications
3
194
0
12
Order By: Relevance
“…Additional proof that infections cause thrombosis comes from associations between infection and subsequent thrombosis in the same specific site, reported for various morbidities, e.g. Lemierre syndrome and cerebral vein thrombosis (Korathanakhun et al , ; Johannesen & Bodtger, ; Yildiz et al , ).…”
Section: Discussionmentioning
confidence: 96%
“…Additional proof that infections cause thrombosis comes from associations between infection and subsequent thrombosis in the same specific site, reported for various morbidities, e.g. Lemierre syndrome and cerebral vein thrombosis (Korathanakhun et al , ; Johannesen & Bodtger, ; Yildiz et al , ).…”
Section: Discussionmentioning
confidence: 96%
“…However, the study that indicated that 64% of patients used anticoagulants for treating such infections did not distinguish between the different types of thrombosis, such as thrombosis of the cavernous sinus, which may require a more aggressive treatment than thrombosis of the internal jugular vein. 17 In our report, the use of enoxaparin with a full dose of warfarin was initiated during hospitalization, and the patient was prescribed oral warfarin at discharge.…”
Section: Discussionmentioning
confidence: 90%
“…An otolaryngologist will be suspicious of Lemierre’s syndrome in patients with severe sepsis from tonsillitis or quinsy that is not responding to antibiotic therapy. It is very rare to have complete resolution of pharyngitis symptoms prior to symptoms from metastatic infection 6. This can mask the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to cavitating lung lesions and empyema despite appropriate antibiotic treatment, as evidenced by this case. Anticoagulation treatment was therefore commenced in an attempt to stop the patient developing respiratory failure from further septic emboli 6. Some authors have suggested commencing anticoagulation therapy if little clinical improvement within 2–3 days of starting treatment or evidence of IJV thrombosis propagation 8 9.…”
Section: Discussionmentioning
confidence: 99%